Monogenea on exotic Indian freshwater fish. 5. First report of pathogenic Gussevia asota (Platyhelminths) from Oscar Astronotus ocellatus (Agassiz 1831) (Perciformes: Cichlidae) - Tripathi, Amit; Matey, Chawan (Zootaxa, 2023)
The neotropical Oscar Astronotus ocellatus has been translocated worldwide as an ornamental fish species with significant economic importance. Twelve adult individuals of A. ocellatus collected from aquaria shops in northern and eastern India were examined for monogenean parasites. Based on morphological methods, all fish samples were found to be infested with Gussevia asota, with a 100% prevalence and high mean intensity [30.16 ± 9.70 (18-48, n=12)]. Molecular analysis of the partial 28S rRNA gene sequence (675 bp), followed by phylogenetic analysis, confirmed the parasite’s identity further. This is the first report of G. asota in India and highlights the need to update and strengthen the quarantine procedures concerning the import of ornamental fish.